Pengaruh Kualitas Pelayanan, Harga dan Promosi Terhadap Keputusan Pembelian Tiket Pesawat pada PT. Citilink Cabang Semarang - Muhammad Farizqi A.B.; Mochamad Taufiq; Sutopo Sutopo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to analyze the influence of service quality, price, promotion and consumer purchasing decisions. The population in this study were all consumers at PT. Citilink Semarang Branch in 2024, totaling 58,249 people, while the sample taken using the Slovin formula resulted in 100 people. Sampling using accidental sampling. The data analysis method used is multiple regression. The results of the analysis show that hypothesis 1 (H1) that service quality has a positive effect on consumer purchasing decisions is proven. This means that the higher the quality of service, the higher the tendency of consumers to make decisions to purchase airline tickets. Hypothesis 2 (H2) that price has a positive effect on consumer purchasing decisions is proven. This means that the more affordable the price offered, the higher the tendency of consumers to make decisions to purchase airline tickets. Hypothesis 3 (H3) that promotion has a positive effect on consumer purchasing decisions is proven. This means that the more intense the promotion from the company, the higher the tendency of consumers to make decisions to purchase airline tickets.